Phosphate Uptake, Mycorrhiza Colonization and Yield of Soybean on Ultisols Affected by Water Stress and Mycorrhiza - Betty Natalie Fitriatin; Anne Nurbaity; Abraham Suriadikusumah (Percetakan Umi Toaha Makassar, 2026)
Mycorrhizal symbiosis can enhance nutrient uptake, especially phosphorus, by plants and increase plants’ drought resistance as well. An experiment was set up to investigate the effects of water stress and mycorrhizal inoculation on phosphate uptake, mycorrhizal colonization, growth, and the yield of soybean. The experiment design used was Factorial Randomized Block, which consisted of two factors. The first factor was water stress, which consisted of three levels, i.e., 100 % field capacity; 75 % field capacity, and 50 % field capacity. The second factor was mycorrhiza, which consisted of three levels, i.e., without mycorrhizal inoculation, 10, and 20 g of mycorrhizal inoculant. The experiment consisted of two units with three replications; the first unit was harvested at the end of the vegetative period to observe plant uptake of phosphorus, percentage of mycorrhizal infection, and dry weight of soybean, and the second unit was harvested at the end of the generative period to find out the yield of soybean. The results of this experiment showed that there was no interaction effect between water stress and mycorrhizal inoculation on plant uptake of phosphorus, percentage of mycorrhizal infection, dry weight, and yield of soybean. Water stress decreased phosphate uptake, percentage of mycorrhizal infection, dry weight, and yield of soybean. Mycorrhizal inoculation increased phosphate uptake and the percentage of mycorrhizal infection.